Diagnosis and treatment of renal neuroendocrine tumors: a case report and literature review - Wang, ShiHui; Li, JiongMing; Yang, JieShun; Li, Pei (Frontiers in Oncology, 2025)
Renal neuroendocrine tumors (NETs) are rare due to the absence of neuroendocrine cells in the kidney. Preoperative diagnosis is challenging often leading to misdiagnosis unnecessary nephrectomy. This study retrospectively analyzed three cases of renal NETs reviewing their diagnosis treatment processes. The first case involved a 46-year-old female presenting with lower abdominal pain diagnosed with a left renal NET (G2) post-surgery. The second case was a 56-year-old female with back pain diagnosed with a renal pelvic NET (G2) after laparoscopic nephroureterectomy. The third case was a 45-year-old female presenting with a palpable mass diagnosed with a right renal NET (G3) with liver metastases. All cases exhibited non-specific clinical presentations imaging findings highlighting the difficulty in preoperative diagnosis. Surgical resection was the primary treatment for non-metastatic cases while the metastatic case received a combination of surgical medical therapy. This study emphasizes the need for improved preoperative diagnostic methods to avoid aggressive surgical approaches to preserve renal units when possible. Further research is required to develop effective diagnostic tools treatment strategies for renal NETs.